Overview of Hemoglobin and Hematocrit Levels in Pregnant Women in the First, Second, and Third Trimesters at Kraton Pekalongan Regional General Hospital - Subur Wibowo; Amelia Wulan Febriyanti (INDOGENIUS, 2026)
Background & Objective: Pregnancy is the union of spermatozoa and ovum followed by implantation. Pregnancy with certain signs may indicate the occurrence of dangers that can occur during pregnancy, which if not reported or detected early can cause death to the mother and fetus. One way to keep mothers and babies healthy during pregnancy is by conducting pregnancy checkups. This study aims to determine the levels of hemoglobin and hematocrit in pregnant women in their first, second, and third trimesters at the Kraton Regional General Hospital in Pekalongan Regency. Method: This study used a descriptive design with 30 samples taken using total sampling from pregnant women in their first, second, and third trimesters at the Kraton Regional General Hospital in Pekalongan Regency. Hemoglobin levels were measured using a spectrophotometer, and hematocrit levels were measured using a microhematocrit method. Result: The results showed that pregnant women in the first trimester had hemoglobin levels of 9.18% and hematocrit levels of 31.4%, pregnant women in the second trimester had hemoglobin levels of 12.8% and hematocrit levels of 35.3%, and pregnant women in the third trimester had hemoglobin levels of 13.28% and hematocrit levels of 37.1%. Conclusion: It can be concluded that in the first trimester, there is a decrease in HB and HT levels due to plasma volume increasing faster than the number of red blood cells, and in the second and third trimesters, there is a greater increase in plasma volume than in red blood cell volume.